S52 Computed tomography in the diagnosis of left heart disease in patients with suspected pulmonary hypertension. (15th November 2017) - Currie, B; Johns, C; Chin, M; Elliot, CA; Condliffe, RA; Charalampopolous, A; Rajaram, S; Wild, JM; Kiely, DG; Swift, AJ
Abstract : Background: Identification of patients with left heart disease (LHD) as the cause of pulmonary hypertension is challenging, developing a tool that can identify these patients would reduce unnecessary referral for investigation at specialist centres and may reduce the burden of invasive investigations. The aim was to investigate the capability of computed tomography (CT)-derived metrics for the diagnosis LHD in a cohort of patients with suspected pulmonary hypertension. Methods: Patients with suspected pulmonary hypertension who underwent CT and RHC were identified. Derivation and validation cohorts were randomly constructed to derive and test a binary logistic regression model. All image analysis took place on PACS system blinded to patient's cardiac catheter data and diagnosis. CT measurements of the cardiac chambers and vessels were taken. LHD was defined by increased pulmonary arterial wedge pressure (PAWP) ≥15 mmHg. A second threshold of 18 mmHg defined more advanced LHD. Backward binary logistic regression in a derivation cohort identified a model for predicting Group 2 PH. This model was tested in the validation cohort and compared to individual CT derived variables using receiver operating characteristic curve analysis and chi-square. Results: The CT scans were from 66 different centres and 446 patients were identified, derivation cohort (n=235) and validation cohort (n=211). Left atrial area was found to be most significant individual predictor of elevated PAWP, area under curve (AUC) 0.86, p<0.001, the accuracy was higher for identification of PAWP ≥18, AUC 0.87, p=0.87, p<0.001. Derived regression models did not add diagnostic value AUC in validation cohort 0.87, p<0.001. A limit for enlarged left atrial area was set at 27.5 cm 2 . This had sensitivity 65% and specificity 90% in predicting Group 2 PH using PAWP ≥18 mmHg as a threshold. Conclusions: CT derived left atrial area is a specific predictor of LHD in suspected pulmonary hypertension. Composite models did not increase diagnostic value. Left atrial area on CT may be a useful tool for diagnosing PH-LHD and may reduce unnecessary referrals to specialist PH centres and reduce the number of invasive investigations.